Burden of asthma exacerbations and health care utilization in pediatric patients with asthma in the US and England. Issue 2 (28th March 2020) - Gokhale, Mugdha; Hattori, Takako; Evitt, Lee; Lenney, Warren; Nordstrom, Beth; Collins, Jenna; Schultze, Anna; Van Dyke, Melissa K.
Abstract: Background: Data on asthma burden in pediatric patients are limited; this real‐world study investigated exacerbation frequency and health care resource utilization (HCRU) in pediatric asthma patients from the US and England. Methods: Data from pediatric patients (aged 6‐17 years) in the Optum claims database (US) or Clinical Practice Research Datalink with linkage to Hospital Episode Statistics (England) were analyzed. Patients were categorized into four hierarchical groups: treated asthma (patients with ≥1 baseline asthma medication), severe asthma (plus Global Initiative for Asthma Step 4/5), severe refractory asthma ([SRA] plus ≥2 baseline severe asthma exacerbations), and eosinophilic SRA (SRA plus blood eosinophil count ≥150 cells/µL). Exacerbation frequency and HCRU during the 12 months postindex were described. Results: Of 151 549 treated asthma patients in the US, 18 086 had severe asthma, 2099 SRA, and 109 eosinophilic SRA. There were 32 893 treated asthma patients in England, of whom 2711 had severe asthma, 265 SRA, and 8 eosinophilic SRA. In the 12 months postindex, ≥1 exacerbation occurred in 12.4% and 10.8% of patients with severe asthma, and 32.6% and 42.6% with SRA in the US and England, respectively. The proportions of patients with ≥1 asthma hospitalization in the 30 days after the first asthma exacerbation were 2.7% and 4.4% (treated), 3.5% and 8.2% (severe asthma), and 6.0% and 16.8% (SRA) in the US and England, respectively. Conclusion: This study provides insights into current asthma management practices in the US and England and indicates that some patients with severe disease have an unmet need for effective management. Abstract : Real‐world data from the US and England were analyzed to investigate exacerbation frequency and health care resource utilization (HCRU) in pediatric asthma patients. Exacerbation frequency and HCRU tended to increase with asthma severity, indicating that disease burden increases with disease severity. This study provides insights into current asthma management practices in the US and England and indicates that some patients with severe disease have an unmet need for effective management.